2010
DOI: 10.1111/j.1749-6632.2010.05435.x
|View full text |Cite
|
Sign up to set email alerts
|

Afferent control of locomotor CPG: insights from a simple neuromechanical model

Abstract: A simple neuromechanical model has been developed that describes a spinal central pattern generator (CPG) controlling the locomotor movement of a single-joint limb via activation of two antagonist (flexor and extensor) muscles. The limb performs rhythmic movements under control of the muscular, gravitational and ground reaction forces. Muscle afferents provide length-dependent (types Ia and II) and force-dependent (type Ib from the extensor) feedback to the CPG. We show that afferent feedback adjusts CPG opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 43 publications
3
99
0
Order By: Relevance
“…These studies suggested that during the extension phase of locomotion, disynaptic reflexes evoked from group I ankle extensor muscle afferents simultaneously activated hip, knee and ankle extensor motoneurones, thus increasing force production necessary to support the body during stance [24] . Moreover, consistent with the idea that muscle spindles can enhance and reset locomotor activity [25] , stimulation of the leg muscle afferents during fictive locomotion appeared to modulate locomotor phase duration, as well as speed, and gait stability [26] . According to Hasan and Stuart [27] , muscle spindles in active, agonist muscles are able to help foster locomotor stability, because their feedback during stance consistently heightens motoneurone activity, and does so, regardless of walking system studied.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…These studies suggested that during the extension phase of locomotion, disynaptic reflexes evoked from group I ankle extensor muscle afferents simultaneously activated hip, knee and ankle extensor motoneurones, thus increasing force production necessary to support the body during stance [24] . Moreover, consistent with the idea that muscle spindles can enhance and reset locomotor activity [25] , stimulation of the leg muscle afferents during fictive locomotion appeared to modulate locomotor phase duration, as well as speed, and gait stability [26] . According to Hasan and Stuart [27] , muscle spindles in active, agonist muscles are able to help foster locomotor stability, because their feedback during stance consistently heightens motoneurone activity, and does so, regardless of walking system studied.…”
Section: Methodssupporting
confidence: 74%
“…In this regard, Elloway et al [3] concluded that the wide ranging response range of muscle spindles that can be differentially activated by the magnitude of prevailing dynamic gamma efferent feedback potentially helps to raise the sensitivity of primary muscle spindle afferents and their ability to detect departures from the trajectory of the anticipated movement. However, since their optimal efficiency depends on the presence of intact supraspinal control mechanism [57,58] , when this pathway is impaired, the resultant decreased ability to produce the degree of coordination required during locomotion to successfully prevent a slip or trip if encountering obstacles or unexpected surface variations may result in a fall [59] . Arguably, therefore, if the schematic representation depicted in Figure 2 is valid, older people with aging sensory systems, cognitive deficits, sensorimotor disturbances, as well as muscular dysfunction may hence be quite prone to incurring falls during level walking activities, especially out of doors, or if the interior is unfamiliar or an external barrier to safe locomotion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such preparations, the phases of extensor and flexor activity, which roughly correspond to the stance and swing phases of real locomotion (i.e., as opposed to fictive locomotion), respectively, are measured from bursts recorded in peripheral nerves or ventral roots. Results obtained during fictive locomotion have been used to model the functional organization of spinal locomotor networks, socalled central pattern generators (CPGs) (Markin et al 2010;Spardy et al 2011aSpardy et al , 2011bYakovenko et al 2005). The concept of "phase dominance" was introduced to denote the phase that showed the most variation as a function of cycle duration (Fleshman et al 1984;Frigon 2012;Frigon andGossard 2009, 2010;Gossard et al 2011;Yakovenko et al 2005).…”
mentioning
confidence: 99%
“…Locomotor training focuses on adaptation of the Central Pattern Generator (CPG), which is a largely autonomous neural circuit that produces cyclical bursts of pre-determined muscle activation signals [6,7]. The output of the CPG can be measured in the extremities using surface electromyography (SEMG), from which rhythmic patterns can be identified using a statistical classification technique [8].…”
Section: Introductionmentioning
confidence: 99%